Regime próprio de previdência social dos servidores do Estado do Ceará: um modelo de previsão para mudanças na alíquota de contribuição - Miranda, Mônica Silva (2017)
In order to reduce the financial balance in social security of civil servants from Ceará state - RPPS / CE, the Government of Ceará has issued Complementary Law nº 167/2016 with the objective of gradually increasing the tax pay of state (from 22% to 28 %) and of servants (from 11% to 14%) in the period between 2017 and 2019. In the light of this, this dissertation used the time series approach to project the impact of Complementary Law nº 167/2016 about the sustainability of the Ceará state's social security system during the transition period of the tax. In real terms, the projections indicate that the rate change will mean an annual average reduction of 9.89% in the state's pension deficit between 2017 and 2019.